Kinetics of color development in glucose/Amino Acid model systems at different temperatures (Scientia Agropecuaria, 2016)
This study investigated the influence of temperature on the color development of melanoidins formed from a single combination of glucose with amino acid. The selected amino acid, commonly found in apple juice and highly reactive in the Maillard reaction, were asparagine (Asn), aspartic acid (Asp) and glutamic acid (Glu). For this, the color development was evaluated by measuring browning at 420 nm and color measurements by spectrophotometry and colorimetry methods. The effect of temperature on the color intensity, the absorption of melanoidins were also measured at different wavelengths (280, 325, 405). The value of melanoidins formed from all model systems was located on a dominant wavelength of 325 nm, the ultra violet zone of the diagram. A first-order kinetic model was applied to L* and the evolution of color difference ΔE*. In addition, a*, b* values, significantly differences were found in the glucose/aspartic acid model system in the brown-red zone. Therefore, the color development of the melanoidins was influenced by the type of amino acid and temperature, and it is thought that the a* and b* values can be used to explain the differences among the amino acid in the color development of melanoidins.